1994
DOI: 10.1111/j.1749-7345.1994.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Carnitine and Lysine Affect Channel Catfish Lipid and Protein Composition

Abstract: The effects of carnitine (L‐carnitine) at 0.1% were tested at three levels of dietary lysine (L‐lysine‐HCl), 1.1, 1.4 or 1.7%, with fingerling channel caffish. Semipurified diets containing 30% protein and 3.44 kcal digestible energy/g were fed for 8 wk in flow‐through water at 26.5 ± 0.5 C. Carnitine did not significantly (P > 0.71) affect channel catflsh weight gain over this time interval. Weight gain was less when 1.1% dietary lysine was fed without supplemented carnitine than when diets contained 1.4 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 18 publications
8
60
0
Order By: Relevance
“…It has been reported that there was a trend toward a reduction in fillet lipid level in channel catfish 9 blue catfish hybrids fed diet containing 500 mg/kg L-carnitine supplementation (Li et al 2007). On the other hand, addition of dietary L-carnitine reduced lipid content of muscle in Atlantic salmon (Ji et al 1996), channel catfish (Burtle and Liu 1994) and European seabass juveniles (Santulli and d'Amelio 1986). Dias et al (2001) reported that dietary supplementation of L-carnitine did not affect whole-body composition of 250 g seabass.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there was a trend toward a reduction in fillet lipid level in channel catfish 9 blue catfish hybrids fed diet containing 500 mg/kg L-carnitine supplementation (Li et al 2007). On the other hand, addition of dietary L-carnitine reduced lipid content of muscle in Atlantic salmon (Ji et al 1996), channel catfish (Burtle and Liu 1994) and European seabass juveniles (Santulli and d'Amelio 1986). Dias et al (2001) reported that dietary supplementation of L-carnitine did not affect whole-body composition of 250 g seabass.…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental dietary L-carnitine showed positive effects in terms of growth rate and food conversion ratio of red sea bream (Chatzifotis et al, 1995;, tilapia Dikel et al, 2003), European sea bass (Santulli and D'Amelio, 1986) and African catfish (Torreele et al, 1993), hybrid striped bass (Twibell and Brown, 2000). In contrast dietary carnitine did not affect weight gain of the channel catfish (Burtle and Liu, 1994), rainbow trout ( Rodehutscord, 1995) or Atlantic salmon (Ji et al, 1996). However, in the present study, growth rate and FCR of rainbow trout have been positively affected by carnitine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing carnitine in fish have indicated growth improvement in sea bass (Santulli and D'Amelio, 1986), African catfish (Torreele et al, 1993), carp (Becker and Focken, 1995) red sea bream (Chatzifotis et al, 1995), white prawn and hybrid sea bass (Twibell and Brown, 2000). On the other hand, inclusion of different levels of L-carnitine in diet has negligible or even negative effects on growth in warm water (Ozorio, 2001;Burtle and Liu 1994;Harpaz et al, 1999;Dzikowski et al, 2001;Schlechtriem et al, 2004) and cold water fish species (Rodehutscord, 1995;Ji et al, 1996;Gaylord and Gatlin, 2000). These differences of results between species suggest that the effects of dietary carnitine supplements are associated with different factors such as age, fish size, experiment period, feed composition and levels of supplement.…”
Section: L-carnitinementioning
confidence: 99%
“…In addition, Mohseni et al (2008) showed that growth performance of sturgeon (Beluga beluga) was improved when fish was fed 300 mg L-carnitine kg -1 diet. Nevertheless, little or no effect of L-carnitine supplementation on growth was observed in other species (Burtle and Liu, 1994;Ji et al, 1996;Chatzifotis et al, 1997;Harpaz et al, 1999;Gaylord and Gatlin, 2000;Dzikowski et al, 2001;Ozório et al, 2001;Schlechtriem et al, 2004). The contradictory results may be an effect of different experimental conditions, such as the duration of experiments, level of L-carnitine supplementation, fish size, leaching of carnitine, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the density had been deliberately increased to expose fish to extreme stress, as suggested by Harpaz (2005), L-carnitine did not improve fish growth or feed conversion efficiency. Some authors also reported that carnitine did not elicit any measurable effect on growth for a range of warmwater (Burtle and Liu, 1994;Harpaz et al, 1999;Dias et al, 2001;Dzikowski et al, 2001;Ozorio, 2001;Schlechtriem et al, 2004) and coldwater fish species (Rodehutscord, 1995;Ji et al, 1996;Chatzifotis et al, 1997;Gaylord and Gatlin, 2000). Harpaz (2005) concluded that these contradictory results are associated with different factors such as age, fish size, experimental period, feed composition and levels of supplement.…”
mentioning
confidence: 99%